2018
DOI: 10.29359/bjhpa.10.4.14
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical activity on glycaemic control in children and adolescents with type 1 diabetes mellitus participating in diabetes camp

Abstract: Background: Children with type 1 diabetes (T1D) are at high risk of having insufficient physical activity during school days and, thus, the importance of special program in promoting regular physical exercise has been largely emphasized. Therefore, this study examined the levels of physical activity and glycemia control in children with T1D, with particular focus on the relative contributions of regular physical education and physical activity program during the diabetes camp.Material and methods: Ninety-eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This was the case despite the fact that the children in the intervention group had attended the diabetes sports camp. This finding is consistent with findings from an earlier study [ 20 ] suggesting that participation in camps does not promote immediate increases in levels of PA. On the other hand, in the research conducted by Sikora et al, the positive effects on PA were observed three to six months after the end of the camp. This evidence may suggest a delay in the effects of the camp on the behavior of young people.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was the case despite the fact that the children in the intervention group had attended the diabetes sports camp. This finding is consistent with findings from an earlier study [ 20 ] suggesting that participation in camps does not promote immediate increases in levels of PA. On the other hand, in the research conducted by Sikora et al, the positive effects on PA were observed three to six months after the end of the camp. This evidence may suggest a delay in the effects of the camp on the behavior of young people.…”
Section: Discussionsupporting
confidence: 93%
“…A comparative study in children with T1DM who either participated in diabetes camps or attended regular schools showed that the first group met the recommended number of steps per day. In addition, it was discovered that attending diabetes camps offered considerable benefits for health-related issues for children diagnosed with T1DM [ 20 ]. On the other hand, participation in diabetes camps did not seem to improve quality of life, anxiety, or psychological status in any of the previous investigations [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients should receive more information on how to adapt their diet and insulin therapy to their physical activity. Research carried out among participants of diabetic children's camps indicate good tolerance of high levels of physical activity (Sikora, et al, 2018). This shows a need of the active presence of a physical education teacher in a group of people supporting a child with type 1 diabetes in school, i.e.…”
Section: Dyskusjamentioning
confidence: 99%
“…Foods such as potatoes, refined grains and those containing added sugars are harmful and have been linked to higher glycaemia, inflammation and cardiometabolic risk [30,31]. Furthermore, it has been shown that less than a fifth of adults with T1D manage to meet physical activity recommendations [32,33], despite evidence that regular physical activity in this population group provides many physiological and psychological benefits [34], whilst reducing daily insulin requirements [35].…”
Section: Introductionmentioning
confidence: 99%